1997
DOI: 10.1086/286088
|View full text |Cite
|
Sign up to set email alerts
|

The Light: Nutrient Ratio in Lakes: The Balance of Energy and Materials Affects Ecosystem Structure and Process

Abstract: The amounts of solar energy and materials are two of the chief factors determining ecosystem structure and process. Here, we examine the relative balance of light and phosphorus in a set of freshwater pelagic ecosystems. We calculated a ratio of light: phosphorus by putting mixed-layer mean light in the numerator and total P concentration in the denominator. This light: phosphorus ratio was a good predictor of the C:P ratio of particulate matter (seston), with a positive correlation demonstrated between these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

47
581
11
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 417 publications
(648 citation statements)
references
References 57 publications
47
581
11
2
Order By: Relevance
“…Therefore, previous generalizations that macrophyte-dominated communities often exhibit higher levels of export (Duarte and Cebrian 1996;Cebrian 1999) than microalgal communities seem to be an oversimplification. Because the magnitude of autotrophic carbon exported does not differ among the community types compared here, I suggest that all these types potentially have a similar importance in fuelling allochthonous (i.e., out of the community) secondary production, although the nutritional quality of the material exported (internal nutrient concentration) needs also be considered (Sterner and Hessen 1994). The results also identify marshes as a larger organic carbon trap than the other community types, with the exception of seagrass beds and mangroves, because they accumulate a greater magnitude of refractory detritus.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, previous generalizations that macrophyte-dominated communities often exhibit higher levels of export (Duarte and Cebrian 1996;Cebrian 1999) than microalgal communities seem to be an oversimplification. Because the magnitude of autotrophic carbon exported does not differ among the community types compared here, I suggest that all these types potentially have a similar importance in fuelling allochthonous (i.e., out of the community) secondary production, although the nutritional quality of the material exported (internal nutrient concentration) needs also be considered (Sterner and Hessen 1994). The results also identify marshes as a larger organic carbon trap than the other community types, with the exception of seagrass beds and mangroves, because they accumulate a greater magnitude of refractory detritus.…”
Section: Discussionmentioning
confidence: 92%
“…Wang et al [1996] found carbon ae between 70 and 94% depending upon phytoplankton food species). Furthermore, estimates of nutrient recycling ratios based on Sterner's (1990b) equations assume that both elements are accumulated by the consumer with equal efficiencies, which may not be a realistic assumption. Under the typical freshwater conditions of our study (seston N : P >> zooplankton N: P), much of the N ingested cannot be used if the consumer is to maintain homeostatic body N : P P accumulation efficiency (Pae) should be maximized, particularly if zooplankton are P limited, but there would be little benefit from increasing N accumulation efficiency (Nae) except under circumstances of very low Nae (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We thus test the hypothesis that differences in relative phytoplankton N and P deficiency in lakes and oceans are driven by differences in zooplankton body N : P and therefore relative rates of N and P recycling, of dominant zooplankters in marine and frcshwaters (Elser et al 1988). Alternatively, food-quality constraints, reflected in differences in seston C : N, C : P and N : P relative to zooplankton body composition, could be a key factor in driving zooplankton community composition (Sterner 1990b;Sterner et al 1992). General patterns regarding these parameters have been reported previously (Elser and Hassett 1994).…”
mentioning
confidence: 80%
See 2 more Smart Citations